The factorized form of the expression using the difference of two square is 2(x+3)(x-3)
Given the following function expressed as 2x^2 - 18
Factor out the GCF
2(x^2 - 9)
This can be written as
2(x^2 - 3^2)
According to the difference of two square, a^2 - b^2 = (a+b)(a-b)
Simplify
2(x^2-3^2) = 2(x+3)(x-3)
This given the factorized expression of 2x^2- 18
Learn more on factoring here: brainly.com/question/24734894
#SPJ2
Hi Brainiac
2x² - 18
First you need to factor out the common term which is 2
2(x²-9)
Now factor x²-9
2(x+3)(x-3)
I hope that's help:0
B) 6 years old
C) 8 years old
D) 10 years old
Answer:
The answer is B) 6 years
Step-by-step explanation:
First of all, build an equation. With the given problem, you can come up with:
s + c = 16
In which interprets that both their ages summed up are 16. Secondly,:
s = c + 4
After you will use the typical system of equations to solve. So, plug in the second equation to the first, where s will become c + 4, and the equation is now:
c + 4 + c = 16
And finally, solve for Charmaine's age.
2c + 4 = 16
-4 -4
-----------------
2c = 12
c = 6
Answer:6 years old
Step-by-step explanation: